Introduction to a Landscape Analysis of Multisectoral Approaches for Prevention and Control of Infectious and Vector-Borne Diseases. (29th October 2020) - Fouque, Florence; Gross, Karin; Leung, Zee; Boutsika, Konstantina
Abstract: The Swiss Development Cooperation, Canada's International Development Research Centre, the Swiss Tropical Public Health Institute, and the UNICEF/United Nations Development Programme (UNDP)/World Bank/World Health Organization (WHO) Special Programme for Research and Training in Tropical Diseases (TDR) collaborated on a project to review, understand and promote the use of multisectoral approaches (MSAs) in the prevention and control of vector-borne diseases (VBDs). The objectives of the project were to support a landscape analysis of how MSAs have been used in the prevention and control of VBDs; to develop a theoretical framework for guiding the implementation of interventions; and to test the recommendations in real-life conditions. To realize these objectives, the project supported several activities, including commissioning a series of scientific reviews on MSAs in 5 thematic areas, sharing the key findings of these reviews in workshops and events, and developing a guidance framework for the implementation of MSAs. These activities have produced the theoretical framework that will be tested in real-life conditions through the support of case studies. The collaboration on implementing multisectoral activities against VBDs will continue among TDR, the Swiss Tropical Public Health Institute, and new partners such as the WHO Water Sanitation and Hygiene Group, UNDP, and UN-Habitat, in order to face the challenges identified and propose solutions tailored to specific contexts. The prevention and control of VBDs require strong and adapted MSAs with the full participation of all relevant sectors.